Binder-free heterostructured MWCNTs/Al2S3 decorated on NiCo foam as highly reversible cathode material for high-performance supercapacitors. (20th April 2020) - Baig, Mutawara Mahmood; Gul, Iftikhar Hussain; Khan, Muhammad Zarrar; Mehran, Muhammad Taqi; Akhtar, Muhammad Saleem
Abstract: Two-dimensional metal sulfides are potential electrodes for supercapacitors, yet for the real-world applications, the cycle stability and performance rate require further improvement. An efficient approach to improve the performance rate of the supercapacitors is to develop a binder-free high capacitance electrode material with hierarchical and porous architectures. Herein, a binder-free heterostructure MWCNTs/Al2 S3 directly grown on NiCo foam as a cathode material was reported. The electrode materials were characterized using X-ray diffraction, scanning electron microscopy and BET analyzer. The pseudocapacitive behavior was investigated by cyclic voltammetry and galvanostatic charge-discharge, demonstrating the excellent performance and reversibility of the electrodes. The maximum specific capacitance of the developed heterostructured MWCNTs/Al2 S3 electrode was 2484 F/g or 414 mA h/g and energy density of 124 Whkg −1 at a power density of 250 W kg-1, with 99.8% capacitance retention after 20, 000 cycles. This study also reveals the significant electrochemical properties of the MWCNTs/Al2 S3 positive electrode using an asymmetric supercapacitor in a two-electrode configuration. The supercapacitor can operate at a potential window of 1.1 V, approximately twofold broader than symmetric device. These results show that the use of binder-free MWCNTs/Al2 S3 electrode can potentially be used in asymmetric supercapacitors, leading to improved electrochemical properties.